POTENCY OF FOOD PRODUCTION BASED ON INTEGRATED FARMING TO SUPPORT FOOD SUFFICIENCY - Rahayu Relawati (UNEJ e-Proceeding, 2012)
Food production is important to support food sufficiency. Meanwhile integratedfarming is a farming system purposed to optimize production factors in increasing yieldand also to eliminate agricultural waste, ideally it becomes zero waste. The researchpurpose was to measure food production from farm management which applied integratedfarming. This research result is used to predict food sufficiency in the region level. Theresearch was done at Batu and Malang Regency, East Java. The research subjects arefarmers who applied integrated farming, namely applying cultivation of crops andlivestock in one management and they use the waste from livestock as input of farming,vice versa. Primary data was taken by structured and indepth interview. The research showed that integrated farming can produce high yield of vegetable and dairy cattle. Meanwhile their usage of each farm waste can reduce (save) the farm cost. The success ofintegrated farming to increase yield at farm level can be used to predict food sufficiency atthe region level. If the implementation is getting wider at the region, they also can increasetheir food production. By using simulation, data of food production at farm level can beused as prediction of food production map at region level.